2015
DOI: 10.3109/13651501.2014.1002501
|View full text |Cite
|
Sign up to set email alerts
|

Towards a pragmatic and operational definition of relapse in schizophrenia: A Delphi consensus approach

Abstract: A better understanding of the definition of relapse in schizophrenia is necessary to improve effective prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
13
0
4
Order By: Relevance
“…There are numerous previous studies in which the investigators review the literature and seek the counsel of experts to develop definitions and clarify terminology. Most of these relate to clinical or physiological definitions [ 54 56 ]. A few explorations of definitions relate to concepts such as quality of life [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous previous studies in which the investigators review the literature and seek the counsel of experts to develop definitions and clarify terminology. Most of these relate to clinical or physiological definitions [ 54 56 ]. A few explorations of definitions relate to concepts such as quality of life [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parenting strategies for reducing the risk of adolescent depression and anxiety disorders (Yap et al, 2014) Improve cultural competence Culturally appropriate mental health first aid to an Aboriginal or Torres Strait Islander adolescent (Chalmers et al, 2014) Develop policy How tertiary education institutions can support students with a mental illness (Reavley et al, 2013) Develop a health economic model Cost-effectiveness of 3 antidepressants in major depressive disorder in the UK (LenoxSmith et al, 2009) Define a concept Definition of relapse in schizophrenia (San et al, 2015) Develop a scale Item content for a geriatric depression inventory appropriate to Chinese culture (Xie et al, 2015) Improve classification or diagnosis Clinical subtypes of core premenstrual disorders (Ismail et al, 2013) Determine epidemiology (prevalence, risk factors)…”
Section: Type Of Use Examplementioning
confidence: 99%
“…87,89 Conversely, we sought to define the duration of a stable condition prior to relapse, and this suggested that a period of 6 months was more favorable than a period of 12 months, which is consistent with the findings of other studies. 5 Few respondents agreed that an increase in the level (frequency) in the frequency of psychiatric consultations.…”
Section: Relapsementioning
confidence: 99%
“…The core characteristics of relapse are identified as follows: the reappearance of schizophrenia symptoms in patients who have been symptom-free after an initial episode (there is need to consider a minimum period of time for reappearance of schizophrenia symptoms), worsening of clinical status severity, worsening of functioning, and reappearance of positive symptoms. 5 Recovery, the ultimate goal of treatment, should include functional recovery as well as symptomatic improvement. Recovery is defined as adequate function and not impeded social and occupational function social and occupational function, but no clear consensus on the definition of recovery exists either.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation